A eclosão do discurso constitucional chileno: os estalidos sociais como ponto de não retorno - MARIA, Vitória Luiza Leal de (2024)
Chile, an Andean country popularly known for being the most stable democracy in South America due to its high economic development and its "peaceful" transition to democracy, is now engulfed by a popular wave that emerges in the outskirts of Santiago and spreads throughout its territory. The institutionalization of neoliberal politics during Pinochet's dictatorship and its persistence in Chile's public sphere, even after the fall of the military, contributed to the occurrence of the "estalido" phenomenon, in which various social actors took to the streets of the country for a common cause: to expose popular dissatisfaction with the State's institutional omission in acting as a guarantor of rights in the face of the prevalence of neoliberal technocracy and the urgency of envisioning a new constituent discourse as a path to emancipation.